قومی ریاست کا مغربی تصور اور مسلم معاشرے پر اس کے اثرات:عصر حاضر کے تناظر میں ایک مطالعہ: Western Concept of National State and Its Impact on Muslim Society: A Study in Contemporary Perspective (Al-Qamar, 2021)
When religion was ousted in the collective affairs of man. The head of human unity was shattered. The slogan of nationalism was used to unite man   in the struggle for unity. This gave rise to the idea of nation-state. This is explained in the article that the nation-state is formed on the basis of color, language and homeland which is free and independent state. The effects of the nation state on Muslim society are discussed in detail. Muslims take pride in adopting western civilization. Instead of following Islamic teachings. New political system of democracy is practicing in many Muslim countries, which is not compatible with the Islamic system of politics.
Keywords: Nation-State; west; nationalism; Muslim society